Реформування системи категорій земель для цілей оподаткування на підставі міжнародного досвіду - Серебрянський, Дмитро Миколайович; Огороднікова, І. І.; Дмитро Серебрянський (НДІ фінансового права, 2014)
У статті проведено ґрунтовний аналіз та узагальнення міжнародної законодавчої практики уніфікації видів земель, що підлягають оподаткуванню. З урахуванням міжнародного досвіду визначено можливі шляхи розробки ефективної системи категоризації земель для цілей оподаткування в Україні.

This article provides a detailed analysis and synthesis of an international legal practice unification types of land subject to taxation by. Based on international experience considered and identified possible ways to develop an effective system of categorization of land for tax purposes in the Ukraine. Domestic legislation governing the taxation of land as a separate legal category, characterized koliziynistyu and dispersed fundamental norms of legal acts, such as the Tax Code of Ukraine and the Land Code of Ukraine and at the same time mismatch international legislative practice. The main issues in the analysis to determine the most effective experience a country and, therefore, the implementation of its tax system in Ukraine is the lack of a unified approach to the definition of «payment to the earth» as a separate legal category at the international level as well as a variety of approaches to administer depending on the political and economic situation in a particular country. However, analysis of international law reveals the main ways in which moving state regulation of land relations on taxation and which has specificity. However, we note that the wealth of each state, primarily lies not only in the number of land resources, and in how effectively organized and economic use of appropriate government regulation, including through taxation. Summing up, it should be stressed that the removal of these obstacles that can not be considered payment for land as a full financial basis of local government and regional development, can be addressed by improving regulation outlined above directions and taking into account the proposed suggestions and recommendations.
Keywords: категоризація земель; міжнародний досвід; плата за землю; земельний податок; оподаткування земель різної категорії; законодавство у сфері оподаткування; законодавство у сфері земельних правовідносин; землі сільськогосподарського призначення; land categorization; international experience; land payment; land tax; taxation of lands of various categories; legislation in the field of taxation; legislation in the field of land legal relations; agricultural land